THE USE OF DAIF HADITHS ON VIRTUES OF DEEDS (FAḌĀʾIL AL-AʿMĀL) IN ISLAMIC PREACHING: STUDY OF SOME MAJELIS TAKLIMS IN SOUTH TANGERANG - Rubiyanah Rubiyanah; Nabilah binti Yusof Nabilah Nabilah; Abdul Jalil Jalil Jalil (Peminat Ilmu Ushuluddin, 2022)
This article describes the use of daif hadiths about the virtues of deeds (faḍāʾil al-aʿmāl) used by preachers at four majelis taklims in South Tangerang-Banten. This article is a qualitative, descriptive, and analytic study. This study found that the majority of preachers delivered their preaching regarding the virtues of deeds (faḍāʾil al-aʿmāl) by presenting daif hadiths. They stated that daif hadiths may motivate jemaat (congregations) to do various good deeds as long as they do not contradict the Quran and ṣaḥīḥ hadiths. However, one majelis taklim refuses to use daif hadiths, even for the theme of virtues of deeds, and only uses ṣaḥīḥ hadiths in lectures for its congregation (jemaat).